A potential gender bias in assessing quality of life – a standard gamble experiment among university students - Al Obaidi L; Mahlich J (Dove Medical Press, 2015)
Leath Al Obaidi,1 Jörg Mahlich2,3 1University of Nottingham, School of Economics, Nottingham, UK; 2Health Economics, Janssen KK, Tokyo, Japan; 3Düsseldorf Institute for Competition Economics (DICE), University of Düsseldorf, Düsseldorf, Germany Background: There are several methodologies that can be used for evaluating patients' perception of their quality of life. Most commonly, utilities are directly elicited by means of either the time-trade-off or the standard-gamble method. In both methods, risk attitudes determine the quality of life values. Methods: Quality of life values among 31 Austrian undergraduate students were elicited by means of the standard gamble approach. The impact of several variables such as gender, side job, length of study, and living arrangements on the quality of life were identified using different types of regression techniques (ordinary least squares, generalized linear model, Betafit). Results: Significant evidence was found that females are associated with a higher quality of life in all specifications of our estimations. Discussion: The observed gender differences in quality of life can be attributed to a higher degree of risk aversion of women. A higher risk aversion leads to a higher valuation of given health states and a potential gender bias in health economic evaluations. This result could have implications for health policy planners when it comes to budget allocation decisions. Keywords: quality of life, gender, risk aversion, standard gamble, students